2023
DOI: 10.1101/2023.01.31.526407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome-level genomes of multicellular algal sisters to land plants illuminate signaling network evolution

Abstract: The filamentous and unicellular algae of the class Zygnematophyceae are the closest algal relatives of land plants. Inferring the properties of the last common ancestor shared by these algae and land plants allows us to identify decisive traits that enabled the conquest of land by plants. We sequenced four genomes of filamentous Zygnematophyceae (three strains of Zygnema circumcarinatum and one strain of Z. cylindricum) and generated chromosome-scale assemblies for all strains of the emerging model system Z. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 187 publications
1
55
0
Order By: Relevance
“…MIKC-type genes have so far been found in all the five major clades of charophytes, but not in chlorophytes yet, corroborating the view that they are a genuine ‘synapomorphy’ (shared derived trait) of streptophytes (that is charophytes + embryophytes) [21-23, 27]. This finding strongly suggests that MIKC-type genes originated in the stem group of extant streptophytes when a Type II MADS-box gene acquired a K box by unresolved mutation or recombination events.…”
Section: A Very Brief History Of Mads-box Genesmentioning
confidence: 87%
See 2 more Smart Citations
“…MIKC-type genes have so far been found in all the five major clades of charophytes, but not in chlorophytes yet, corroborating the view that they are a genuine ‘synapomorphy’ (shared derived trait) of streptophytes (that is charophytes + embryophytes) [21-23, 27]. This finding strongly suggests that MIKC-type genes originated in the stem group of extant streptophytes when a Type II MADS-box gene acquired a K box by unresolved mutation or recombination events.…”
Section: A Very Brief History Of Mads-box Genesmentioning
confidence: 87%
“…These MTFs were hence termed MIKC-type proteins, the corresponding genes MIKC-type genes. However, the analysis of the genomes of diverse charophytes -a grade of green algae that represents the closest relatives of land plants (embryophytes) -revealed that they contain Type II gene lineages that have K boxes and others that do not [21][22][23], implying that the terms 'Type II genes of plants' and 'MIKC-type genes' should not be used synonymously anymore. This finding also corroborates the view that the absence of a K-box is not a sufficient criterion for classifying a plant MADS-box gene as Type I (as, unfortunately, can sometimes be seen in the literature).…”
Section: A Very Brief History Of Mads-box Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The last common ancestor of all embryophytes likely possessed many adaptations to living on land; further, being the last common ancestor, it had the genetic chassis that underpins traits that count among the synapomorphies of the land plant clade. Recent comparative (functional) genomic studies have revealed that various traits—or at least the genes that underpin these traits in land plants—that were considered embryophyte‐specific are also found in streptophyte algae (Hori et al, 2014; de Vries et al, 2017, 2018; Nishiyama et al, 2018; Feng et al, 2023). These include genes for phytohormone signaling cascades (Hori et al, 2014; de Vries et al, 2018; Nishiyama et al, 2018; Cheng et al, 2019; Jiao et al, 2020), transcription factors (Wilhelmsson et al, 2017), specialized metabolism (Rieseberg et al, 2023), and biotic interactions (Delaux et al, 2015; Delaux and Schornack, 2021).…”
Section: Genomic Signatures Of Streptophyte Algal Stress Physiologymentioning
confidence: 99%
“…Functional work on the PYL homolog of Zygnema revealed a partial mechanistic conservation: while PYL does interact with its downstream target, PP2C, this interaction is not modulated by ABA (Sun et al, 2019). Genomic data have confirmed the presence of PYL homologs in several zygnematophytes (Cheng et al, 2019;Feng et al, 2023). Hence, the question of how the PYL-PP2C signaling cascade contributes to the molecular physiology of zygnematophytes remains wide open.…”
Section: Genomic Signatures Of Streptophyte Algal Stress Physiologymentioning
confidence: 99%